Sustainable Finance And Investment Efficiency: A Literature Review - Wijayanti, Risna; -, Hasmirati (AMAR (Andalas Management Review), 2024)
The review addresses significant research gaps by examining the impact of corporate social responsibility (CSR) practices and environmental, social, and governance (ESG) disclosures on investment outcomes. It investigates the mediating role of optimal investment in linking business sustainability performance to corporate financial performance, and the influence of corporate governance characteristics, such as CEO duality, on investment efficiency. The study systematically reviews literature from 2020 to 2024, utilizing sources from the Scopus database, and identifies key themes and trends. Findings indicate that integrating sustainable finance principles, including ESG performance metrics and green financial practices, can enhance investment efficiency, reduce financial constraints, and promote transparency. The study highlights the significance of robust governance frameworks and investor trust in achieving sustainable financial practices and improving financial performance, particularly in emerging markets. This review contributes valuable insights for policymakers, investors, and corporate managers aiming to enhance investment efficiency through sustainable practices.